Antitumor and genotoxic effects of lactoferrin in Walker-256 tumor-bearing rats - Chekhun, V.F.; Storchai, D.M.; Todor, I.N.; Borikun, T.V.; Lukianova, N.Yu. (Experimental Oncology, 2018)
Aim: To investigate the influence of exogenous lactoferrin (LF) on tumor growth, energy and lipid metabolism of Walker-256 carcinosarcoma and to assess genotoxic effects of LF. Materials and Methods: The study was performed on Walker-256 tumor-bearing rats. Total lipids and phospholipids were determined by thin-layer chromatography. Comet assay was used to investigate the genotoxic effects of LF. Results: Daily i.p. administrations of exogenous LF at concentrations of 1 mg/kg and 10 mg/kg starting from the 4th day after tumor transplantation suppressed growth of Walker-256 carcinosarcoma by almost 44%. After treatment with recombinant LF in both doses, the phospholipid composition of Walker-256 carcinosarcoma cells was changed (3-fold increase of phosphatidylethanolamine, 3.4-fold increase of phosphatidylcholine, and 1.8-fold increase of sphingomyelin, while the cardiolipin content decreased by 67%. Exogenous LF was not genotoxic for bone marrow cells (as assessed by the ratio of PCE/NCE, number of micronuclei) and peripheral blood lymphocytes (percentage of DNA in the tail of a comet) in Walker-256 carcinosarcoma-bearing rats. Conclusion: Exogenous LF caused the inhibition of Walker-256 carcinosarcoma growth and a decrease in the microviscosity of plasma cell membranes, and exerted no genotoxicity toward bone marrow cells and peripheral blood of experimental animals. Key Words: lactoferrin, breast cancer, Walker-256 carcinosarcoma, phospholipid content, genotoxicity.